Factors associated with physical frailty syndrome among community dwelling elderly in Kuala Lumpur, Malaysia - Norazman, Camilla Wahida (2020)
Frailty is a multidimensional syndrome which is a concerned in the geriatric field worldwide due to its aggravating effect on the physical and mental function of elderly. It is commonly described as a physiological state of increased susceptibility to stressors due to decline in multiple physiologic reserves and dysregulation. The main objective of this study is to determine the prevalence and factors associated with frailty syndrome among community dwelling elderly. This is a cross-sectional study, conducted among elderly who resided in Projek Perumahan Rakyat (PPR) Kuala Lumpur. Ten PPR were randomly chosen and the elderly who fulfilled the criteria were recruited in the study. The inclusion criteria of the study population were community-dwelling elderly aged 60 years and above who resides in PPR Kuala Lumpur and able to ambulate without personal assistance. The exclusion criteria include the following: presence of severe sensory deficits for locomotion, communication, drawing and writing; present of Alzheimer disease; unstable medical conditions and presence of terminal illness. The selection of respondents from each PPR was done using the proportionate sampling method. Elderly residents from each PPR were selected based on the proportion from the total elderly for all 10 PPR. Respondents who were eligible were invited to participate in the study. Two days prior to the study allocation, respondents were reminded through phone calls on the date of program and to fast overnight a day before. All invited respondents were gathered in a community hall for the data collection procedure. Frailty status was assessed using the Fried Phenotype criteria of frailty which classified the index into three states of robust, pre-frail and frail. The phenotype composites assessed in the frailty assessment were shrinking, weakness, exhaustion, slowness and low physical activity. The covariates that were hypothesized to be the predictors of frailty were the present of chronic disease, depression, functional disability, malnutrition, low nutrients intake, poor anthropometric measurements and abnormal biochemical parameters. The measurements of anthropometric assessments were performed in accordance to the guideline. The biochemical parameter included in this study are haemoglobin, glucose, hbA1c, lipid profile and C-Reactive protein. Multinomial logistic regression analysis was employed to determine the significant predictors of frailty syndrome. Three hundred and one elderly were recruited in this study with a mean age of 67.08 + 5.536 years ranged from 60 to 84 years old. Majority of the respondents were female (69.4%) and Malay (70.8%). Based on the Malaysia income classification, most of the respondents laid in the lower income classification of poverty (<RM970) with mean monthly income of RM 959.96 + 817.10. The prevalence of frailty and pre-frail from the study population were 15.9% and 72.8% respectively, which women appeared to be at high risk of frailty. Half of the respondents were found to be physically dependent (51.5%) and 15% of the them were cognitively declined. Almost one third of the respondents were at risk of malnutrition (29.6%) and 3.3% were malnourished. The dietary intake of the respondents was compared against Recommended Nutrient Intake (RNI 2017) intake recommendation for Malaysian elderly; majority of them achieved the minimum intake of macronutrients, although notable minute intakes were observed for micronutrients namely folate, potassium and magnesium. More than half of the respondents were reported to be overweight (39.2%) and obese (25.9%) with mean BMI of 27.52 + 5.48 kgm-2. Respondents were presented with high fasting blood glucose (37.5%) and total cholesterol (76.7%) during the data collection. The multivariate analysis revealed that the frailty may be determined by increasing age [OR=1.338, CI: 1.159 – 1.545], lower household income (CI: 0.332, CI: 0.136 – 0.762), being at risk of malnutrition [OR=7.300, CI: 1.747 – 30.509], wasting (low skeletal muscle mass) [OR=0.760, CI= 0.694 – 0.990], high serum CRP level [OR= 1.036, CI= 1.002 – 1.020] and low intake of energy [OR= 0.991, CI= 0.975 – 0.998], protein [CI: 0.937, CI: 0.879 – 0.998], MUFA [0.679, CI= 0.642 – 0.983], PUFA [OR=0.591, CI= 0.415-0.841] and vitamin C [OR=0.981, CI=0.964 – 0.997]. In conclusion, the present study showed those elderly with increasing age, lower household income, being at risk of malnutrition, low skeletal muscle mass, high serum CRP and low intake of energy, protein, MUFA, PUFA and vitamin C were at higher likelihood of being physically frail. Future intervention may be considered these identified parameters into the action plan. More studies are needed to substantiate the present finding by the inclusion of older adults with heterogeneous background for better understanding on the concept of frailty.